Właściwość sądów w sprawach karnych w Polsce w latach 1928–1939 - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The Code of Criminal Procedure of 1928 provided three types of jurisdiction: material, topical and functional. In general, legal solutions adopted in the Code including provisions on material jurisdiction should be viewed positively. The regulations covered all the cases the Polish courts could hypothetically come across in practice, procedurally solving many issues connected with it. The most important cases included: the invalidity of judgments issued by the improper court, the jurisdiction of the magistrates courts, the determination of the topical jurisdiction of the courts, the aggregate consideration of cases, and resolving conflicts of jurisdiction between common and military courts. Few of their infirmities were cured either by amending the Code, or through judicial decisions especially the Supreme Court. The functioning of the rules on jurisdiction contained in the Code of Criminal Procedure, was closely linked with the provisions of the Criminal Code of 1932 and the Law on Courts of 1928. In total, they were one of the best parts of the Code of Criminal Procedure of 1928, contributing to quite efficient — in the years 1918–1939 — course of proceedings and functioning of justice in criminal cases.
Keywords: jurysdykcja w sprawach karnych; sprawy karne; kodeks postępowania karnego; spory jurysdykcyjne